Bibliometric Analysis of Publications on Cultural Heritage Management - Ayvaz, Ebru; Halaç, Hicran Hanım (Journal of History Culture and Art Research, 2023)
Values that reflect the cultural accumulation of societies which were transferred from the past are called cultural heritage. The concept of cultural heritage management emerges in preserving and transferring cultural heritage values to future generations. In order for conservation to be sustainable, in addition to social awareness, it is necessary to create social awareness and awareness for future generations. One of the important steps in this regard is the studies in the literature on cultural heritage management. In this context, for the definition of research terms, related to digital design research in the Scopus database; A systematic literature review was conducted using the bibliometric analysis method using the keyword combination “cultural heritage management” (Title, Abstract, Keywords) AND “conservation” (All Fields) OR sustain* (All Fields). As a result of the keyword search combinations dated 31.12.2022 as the last date of data collection, 442 publications were reached. Results that have been mapped with bibliometric network diagrams obtained from the VOSviewer (VOS) program. Obtained results contain the information of year, language, document type, subject, journal, publisher, keyword, author, country, number of citations and cited authors of the publications. It is expected that this research, which has the characteristics of providing a comprehensive overview of current studies, will contribute to the development of conservation awareness in cultural heritage management by emphasizing the sustainable conservation approach and to the development of the transfer of cultural heritage to future generations by giving direction to the next researches, as well as covering previous researches in a holistic manner.